Concerte mathematics : a foundation for computer science - Graham Ronald L., Knuth Donald E., Patashnik Cren (Dorling kindsley, Delhi, 2009)
Stats/Maths
UGC XIth Five Year Plan 2009-2010
ENGLISH
Keywords: Concerte mathematics : a foundation for computer science; Stats/Maths; Stats/Maths